Development of IoT Based Smart Energy Metering System - Singh, Indermohan (My University, 2017)
In recent years automation utilizing wireless communication has been evolving in major fields of societial life. The smart energy metering system (SEMS) is an innovative system that measures performance parameters of consumers on real time basis and communicates it to remote server. The traditional way of manually taking electricity meter readings and analyzing was a very cumbersome process; consumes lot of time and man power. Internet of Things (IoT) aims to connect multiple embedded systems to Internet, thus enabling an effective way of human-machine and machine to machine communication. This dissertation is an effort to develop an IoT based SEMS which introduces automation in the metering process and overcomes most of difficulties faced in traditional metering process. Proposed model uses two tier communication system in which a multiple smart energy meters communicates to one Data Concentrator Unit (DCU) via Radio frequency transceiver module nRF24L01. The Internet access to DCU can be provided either through Wi-Fi technology, Ethernet or mobile data. Publish/Subscribe messaging system is used to communicate between DCU and remote server. In order to perform all the tasks in easy and flexible way, a user friendly Graphical User Interface (GUI ) has been developed. A complete working model of proposed system is implemented utilizing Atmega 328P microcontroller and Raspberry Pi 3 under Python. The developed system can also be used for report generation and sending bills directly to consumers through SMS and email. It can be operated in manual and auto mode. In manual the authorized person can request data at anytime whereas in auto the information is collected periodically with specified intervals.
Keywords: IoT; Smart Energy Meter; Automatic Metering Instrumentation; Publish Subscribe Messaging System